1987
DOI: 10.1007/bf00383850
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of EEG changes following electroconvulsive therapy in depression

Abstract: Frequency analysis of EEG was made during electroconvulsive therapy (ECT) in patients with depression. Acute effects were quantified by calculating differences of EEG power from before to after the induced seizure, and were found to correlate with the duration of the seizure but not with the time lapse following the seizure. Increases in delta power were much more pronounced at the end of the treatment series than at the beginning. Non-acute effects were quantified as the differences from before the first trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Specifically, there is an increase in the amount of slow wave activity, 13,14 which is frontally predominant. 15,16 Further, these changes are more prominent with bilateral than with unilateral ECT, 14,17 and the amount of EEG slowing is correlated with the number of ECT sessions. In our study, we have not directly examined the EEG changes through the course of ECT.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, there is an increase in the amount of slow wave activity, 13,14 which is frontally predominant. 15,16 Further, these changes are more prominent with bilateral than with unilateral ECT, 14,17 and the amount of EEG slowing is correlated with the number of ECT sessions. In our study, we have not directly examined the EEG changes through the course of ECT.…”
Section: Discussionmentioning
confidence: 94%
“…Three of these patients did not comply with the requirement for repeated sampling and withdrew in the first 2 weeks. The fourth patient was excluded after about 2 weeks of sampling because it was found that, along with the pharmacological treatment change, he also started electroconvulsive treatment (ECT), which affects EEG significantly (18). Participants were recruited through the practicing physicians in the two medical centers.…”
Section: Methodsmentioning
confidence: 99%
“…According to changes in frequency content of the EEG recordings used in this study, two frequency bands (0.5 to 1.7 Hz and 1.8 to 5 Hz) were chosen to extract a feature discriminating between seizure and non-seizure periods. These frequency bands lay in the delta (~0.5 to 4 Hz) and theta (~4 to 8 Hz) bands where most EEG spectrum changes occur during ECT [13].…”
Section: B Methodologymentioning
confidence: 99%